HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MAHASISWA DALAM UPAYA PENCEGAHAN ALERGI MAKANAN DI AKADEMI KEPERAWATAN WILLIAM BOOTH SURABAYA - ., PUTU YENNY, WIJAR PRASETYO (S1 Keperawatan, 2012)
The level of knowledge is the result of the idea and this occurred after the conduct of a particular object sensing. The level of knowledge is affecting student attitudes both positive and negative attitude which can not be separated from the influences of the surrounding environment. Therefore it can be said to be the level of student knowledge is essential to the formation of student attitudes. The purpose of this study was to determine whether there is a relationship between the level of knowledge and attitudes of students in efforts to prevent food allergies. The design of this study is the design of correlation. The number of existing populations of as many as 50 people and the number of samples obtained as many as 44 people with a sampling technique using probability sampling. Data were collected through a questionnaire about the level of knowledge and a questionnaire using a sheet checklist for student attitudes. Then tested by statistical tests with SPSS 16:00 Wilcoxon correlation test with a significance value (0.05). From the test results can be Ï = 0.000 so that Ï < Î±, which means there is a significant relationship between level of knowledge and attitudes of students, although a negative relationship. The level of knowledge can not be measured as a whole so that the level of knowledge that students have a positive attitude can make in addition to having a less pleasant experience, so do not do it anymore.Key word : The level of knowledge, attitude